Роль свободы в процессе развития и воспитания личности - Колесников, М. П. (НТУ "ХПИ", 2009)
In the article is piven the analysis of essence and maintenance frudom in the procen of education of personality. Groundeel, that frudom, as the historical phenomen, must regenerate in the historical process of change of generations, which foresaw the spiritual, moral regeneration of in individuals.
Keywords: общее образование; элитное образование; концепция воспитания; концепция образования; образовательная политика; постмодерн